Impact of Frontline Demonstrations on Yield and Economics of Chickpea in Gariyaband District of Chhattisgarh State (Indian Journal of Extension Education, 2017)
Chickpea is an important rabi season pulse crop. Low productivity of chickpea is due to inappropriate production practices and diminishing soil fertility due to continuous adoption of rice-rice cropping system in the tribal areas of Gariyaband district is a cause of concern at large. To overcome this problem KVK, Gariyaband conducted 52 frontline demonstrations using improved management practices during 2012-13 to 2015-16 in Rabi season in 4 villages (Potia, Amethi, Dhamna, Mahonda) of Gariyaband district. There was an appreciable increase in yield level of 77.5 per cent in chickpea under demonstration plots. The highest seed yield 13.52 q ha-1 was recorded in 2015-16, which was 83.9 per cent more over the farmer’s practice (7.35 q ha-1). The highest extension gap 6.17 q ha-1 was recorded during 2015-16. The lower values of Technology gap (6.48 q ha-1) and Technology index (32.40 %) were recorded during 2015-16. The improved technology gave higher gross returns, net returns with higher benefit cost ratio as compared to farmer’s practices.